Effect of 28 MeV He{2+} Ion Beam and Short-Pulsed 200 keV C{+} Ion Beam Irradiation on Optical Properties of Multilayer Al-Si-N Coatings; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Pavlov S. K. Sergey Konstantinovich; Konusov F. V. Fedor Valerievich; Lauk A. L. Aleksandr Lukyanovich; Sokhoreva V. V. Valentina Viktorovna; Gadirov R. Ruslan; Tarbokov V. A. Vladislav Aleksandrovich (Defect Engineering, Nano-Science and Technology. Poster Session, 2019)
Заглавие с экрана